2007
DOI: 10.1529/biophysj.106.095232
|View full text |Cite
|
Sign up to set email alerts
|

Ion Conduction through MscS as Determined by Electrophysiology and Simulation

Abstract: The mechanosensitive channel of small conductance (MscS) is a membrane protein thought to act as a safety valve in bacteria, regulating the release of ions and small solutes when gated by membrane tension under challenging osmotic conditions. The influence of voltage on channel activation and the functional state depicted by the available crystal structure of MscS remain debated. Therefore, in an effort to relate electrophysiological measurements on MscS and properties of the MscS crystal conformation, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
148
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(162 citation statements)
references
References 71 publications
13
148
1
Order By: Relevance
“…On the other hand, the activation threshold did not change with the membrane potential. Recent studies on MscS have also demonstrated that the activation threshold does not change with voltage (15,27). Thus, voltage-independent activation of ⌬N-MSC1 resembles that of MscS, although MscS and ⌬N-MSC1 may exhibit voltage-sensitive gating under certain experimental conditions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, the activation threshold did not change with the membrane potential. Recent studies on MscS have also demonstrated that the activation threshold does not change with voltage (15,27). Thus, voltage-independent activation of ⌬N-MSC1 resembles that of MscS, although MscS and ⌬N-MSC1 may exhibit voltage-sensitive gating under certain experimental conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Evaluation of these data with the Goldman-HodgkinKatz equation indicated that the ratio of the permeability is g K :g Cl :g Br :g I ϭ 1:7:9:9. This anion preference is stronger than that of MscS, which has a g Cl /g K of 1.2-1.5 (14,15). Decreasing the bath CaCl 2 concentration to 1 mM did not shift the reversal potential, showing that the permeability to Ca 2ϩ was insignificant (Fig.…”
Section: Molecular Identification Of Msc1mentioning
confidence: 84%
“…Another way to determine the likely conductive state of the crystal structure is to simulate the flow of water or ions through the pore. The electrostatic properties and the ion conduction of MscS were also investigated using a new mesoscopic approach (135) for simulations of passive ion transport over long simulation times along with atomistic simulations using biasing electrostatic potentials (136). Both types of simulations showed low conductance for the state of the crystal structure but conductance levels in agreement with experimental data for an open state of the channel.…”
Section: Fig 6 Electrical Recording Of Mscl and Mscs Activity In Tementioning
confidence: 94%
“…Anishkin et al The simulations of the wild type produced a hydrated pore, while simulations of the mutant showed a different hydration pattern and structure of the TM helices that is consistent with the mutants' tendency toward inactivation observed experimentally. Different simulation techniques at the atomistic and mesoscopic level (47,135,136) have also been employed to investigate the role of the cytoplasmic domain in the conductance of anions and cations through the channel.…”
Section: Fig 6 Electrical Recording Of Mscl and Mscs Activity In Tementioning
confidence: 99%
“…Once a nanobubble is formed, it leads to strong and long-ranged hydrophobic forces among the "dry" regions as the system further tries to minimize unfavorable interface area (see for instance the simple plate model above) and can induce quick protein folding and collapse (ten Wolde and Chandler 2002) or stable protein assemblies (Liu et al 2005). Importantly, the evaporation of liquid in the narrow hydrophobic pore region of ion channel proteins (Anishkin and Sukharev 2004, Beckstein et al 2001, Sotomayor et al 2007) seems to be important for the control of physiological ion conductance. The presence of a vapor bubble blocks ion permeation as the ion would have to desolvate to travel through the vapor.…”
Section: Introductionmentioning
confidence: 99%